Increases in RPE Rating Predict Fatigue Accumulation Without Changes in Heart Rate Zone Distribution After 4-Week Low-Intensity High-Volume Training Period in High-Level Rowers - Pind, Rasmus; Hofmann, Peter; Mäestu, Evelin; Vahtra, Eno; Purge, Priit; Mäestu, Jarek (Frontiers in Physiology, 2021)
Purpose: The aim of this study was to investigate: 1) the interaction of training load quantification using heart rate (HR) and rating of perceived exertion (RPE) based methodology; and 2) to investigate the relationship between internal training load parameters and subjective training status (Fatigue) in high-level rowers during volume increased low-intensity training period. Methods: Training data from 19 high-level rowers (age 23.5 ± 5.9 years; maximal oxygen uptake 58.9 ± 5.8 ml·min-1·kg-1) were collected during a 4-week volume increased training period. All individual training sessions were analysed to quantify training intensity distribution based on the HR time-in-zone method (HR Z1, HR Z2, HR Z3) determined by first and second ventilatory thresholds. Internal training load was calculated using session RPE (sRPE) to categorize training load by effort (sRPE1, sRPE2, sRPE3). RESTQ-Sport questionnaire was implemented after every week of the study period. Results: No differences were found between the respective HR and effort-based zone distributions during the baseline week (P>0.05). Compared to HR Z1, sRPE1 was significantly lower in weeks 2-4 (P<0.05), while sRPE2 was higher in Weeks 2-3 compared to HR Z2 (P<0.05) and in Week 4, the tendency (P=0.06) of the higher amount of sRPE3 compared to HR Z3 was found. There were significant increases in RESTQ-Sport stress scales and decreases in recovery scales mostly during weeks 3 and 4. Increases in Fatigue scale were associated with the amount of sRPE2 and sRPE3 (P=0.011 and P=0.008, respectively), while no associations with Fatigue were found for HR-based session quantification with internal or external training load variables. Conclusions: During a low-intensity 4-week training period with increasing volume, RPE based training quantification indicated a shift towards harder rating of sessions with unchanged HR zone distributions. Moderate and Hard rated sessions were related to increases in Fatigue. sRPE and effort-based training load could be practical measures in combination with HR to monitor adaptation during increased volume, low-intensity training period in endurance athletes.